EFFORTS TO IMPROVE SCHOOL CULTURE IN MAS TARBIYAH ISLAMIAH HAMPARAN PERAK DISTRICT, DELI SERDANG REGENCY - Tumiran, Tumiran; Lubis, Sakban; Raidha, Isma (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to determine efforts to improve school culture, inhibiting and supporting factors at MAS Tarbiyah Islamiyah Hamparan Perak, Deli Serdang. The research uses a narrative descriptive qualitative approach. The data sources are (1) primary data, obtained from school principals, teachers/homeroom teachers and students, (2) secondary data, obtained from literature, relevant research, and documents. Data collection by observation, interviews, documentation, and field notes. Data analysis by reducing data, displaying data/presenting data, and verifying/drawing conclusions. The results of the analysis of research data: (1) work programs in an effort to improve school culture: short, medium and long term by applying high dedication, modesty, greeting each other, sincere, mutual cooperation, religious, preserving the environment, cleanliness, tolerance, cooperation, innovate, creative, hospitality, noble character, personality. Efforts to improve school culture at MAS Tarbiyah Islamiyah Hamparan Perak, Deli Serdang have shown significant, accountable results. effective and efficient, (2) Strengthening the behavior and personality, morals and commendable attitudes of students, teachers and stake holders.